2015
DOI: 10.3389/fphy.2015.00055
|View full text |Cite
|
Sign up to set email alerts
|

Light based cellular interactions: hypotheses and perspectives

Abstract: This work investigates the theoretical possibility of interactions between cells via light. We first take a brief look at the previous research done in the past to have a better understanding of the field and the origins of the concept of cellular interactions. Then we identify the different elements essential for interactions between two parties. We then compare the required elements with the known and studied elements and characteristics which are well defined in biology, chemistry and physics. This way we a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 65 publications
0
12
0
Order By: Relevance
“…Underlying hypotheses for such biocommunication role of BAL usually expect that BAL carries information which can be processed by a receiver [46]. Such information could be encoded in the intensity and optical spectrum of BAL [49] or in statistical properties of BAL, if they are any different from random light, as claimed by some authors [45].…”
Section: Statistical Properties Of Biological Autoluminescence (Bal)mentioning
confidence: 99%
“…Underlying hypotheses for such biocommunication role of BAL usually expect that BAL carries information which can be processed by a receiver [46]. Such information could be encoded in the intensity and optical spectrum of BAL [49] or in statistical properties of BAL, if they are any different from random light, as claimed by some authors [45].…”
Section: Statistical Properties Of Biological Autoluminescence (Bal)mentioning
confidence: 99%
“…Bio-photons have been widely proposed as information carriers in brain [63] [115] [116] [117], but also in other tissues [118] [119]. Recently it has been D. K. F. Meijer, H. J. H. Geesink Open Journal of Biophysics shown that incubation of brain slices with glutamate (a major neurotransmitter in the brain) results in the release of red-shifted bio-photons [120] and in a recent PNAS paper that the degree of bio-photon induction in brain slices of various species is highly correlated with the relative intelligence of the species studied [121].…”
Section: Steering By Holographic Memory Hypersphere Of the Individualmentioning
confidence: 99%
“…Underlying hypotheses for such biocommunication role of BAL usually expect that BAL carries information which can be processed by a receiver [46]. Such information could be encoded in the intensity and optical spectrum of BAL [49] or in statistical properties of BAL, if they are any different from random light, as claimed by some authors [45]. At third, statistical properties would represent a completely novel fingerprint for application of BAL in biosensing in biotechnology, agriculture, food industry, and medicine beyond the intensity and optical spectra, hence greatly enhancing application potential of BAL analysis.…”
Section: Statistical Properties Of Biological Autoluminescence (Bal)mentioning
confidence: 99%